Styela cearense n. sp. (Ascidiacea: Styelidae) from the Northeastern Brazilian Coast - Filho, Ronaldo Ruy De Oliveira; Lotufo, Tito Monteiro Da Cruz (Zootaxa, 2015)
The species Styela cearense n. sp. is described from material collected in shallow waters at the Ceará State, Northeastern Brazil. Discussion includes several other species with one gonad on each side of the body, and a tabular key is provided. A set of important anatomical features and their intraspecific variability within the genus is considered, including the number of branchial and stomach folds, the presence of endocarps, and anal border shape.